Ali Rıza Sağman ve tecvit-tilavet anlayışı - Alpuhan, Ayşe Elif (My University, 2018)
Hafız Ali Rıza Sağman, yakın tarihimizin modern ve muhalif kimliği ile temayüz etmiş, özellikle Kur’an kıraati ve musiki alanında yaptığı çalışmalarla farklı bir dil ve üsluba sahip çok yönlü ve aktif ilim adamlarından biridir. Döneminde çeşitli eğitim kurumlarında; tarih, coğrafya, felsefe ve musiki dersleriyle birlikte, Kur’an ve tecvid eğitimi vermiş, gazete ve dergilerde makaleler yazmış, musiki çalışmaları çerçevesinde çeşitli makamlarda besteler yapmıştır.Araştırma konumuz olan “Sağman Tecvidi” onun tecvid alanında kaleme aldığı, kendine has çizgide özgün bir çalışmadır.

Hafız Ali Rıza Sağman, is one of the versatile and active Scholar of short-term history, with modern and opposite identity, having distinct form of language and wording style, especially in the studies of reading and pronunciation of Kur’an and musical art. In his working period, Mr. Sağman has given “Kur’an” and “Tajwid (Art of Reading and Proper Pronunciation in Kur’an)” courses at various education institutions among the other lectures in history, geography and musical art, he has written articles in newspapers and magazines and has also made musical compositions in various modals within the scope of his musical studies. “Tajwid of Sağman” which is the subject of this research study, is a unique and original tajwid at work written by Mr. Sağman.
Keywords: Ali Rıza Sağman; biography; Biyografi; Ku’ran; Kur’an; musical art; musiki; tajwid; tecvid; Tecvit; Tilavet